1987
DOI: 10.1577/1548-8659(1987)7<410:iohohs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrilla on Harvestable Sport-Fish Populations, Angler Use, and Angler Expenditures at Orange Lake, Florida

Abstract: An infestation of hydrilla Hydrilla verticillata caused an 85% reduction in angler effort at Orange Lake, Florida, in 1977 when plant coverage exceeded 80% of the lake. Nonlocal anglers were only 3% of the total number of anglers fishing the lake in 1977, but were 37% of the anglers during 1978 and 1979, when hydrilla coverage was less than 19%. Although angler use of Orange Lake was greatly reduced during the peak 1977 hydrilla infestation, the number of fish caught per hour during 1977 was equivalent to or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…This result is plausible considering the high recreation values and cost-benefit ratios for AIP control reported by other studies (e.g., Milon et al 1986, Colle et al 1987, Adams 2007. For example, the estimated fishing-related economic benefit of just 13 of Florida's public lakes is $59.95 million/yr, but can fall by $29.75 million/yr without consistent invasive aquatic plant control .…”
Section: Statewide Wtpsupporting
confidence: 59%
See 1 more Smart Citation
“…This result is plausible considering the high recreation values and cost-benefit ratios for AIP control reported by other studies (e.g., Milon et al 1986, Colle et al 1987, Adams 2007. For example, the estimated fishing-related economic benefit of just 13 of Florida's public lakes is $59.95 million/yr, but can fall by $29.75 million/yr without consistent invasive aquatic plant control .…”
Section: Statewide Wtpsupporting
confidence: 59%
“…Because AIP often impact nonmarket values for environmental goods and services, the economic damages from AIP goes largely unnoticed unless nonmarket valuation exercises are conducted. Few studies have examined WTP for AIP control, and these have focused on specific lakes or beaches (e.g., Milon et al 1986, Colle et al 1987, Milon and Welsh 1989, Bell et al 1998, Nunes and van den Bergh 2004 or rely on bioeconomic models that do not directly incorporate WTP measures (e.g., Adams and Lee 2007). Prior to this study, little was known about the impact of AIP on recreation in Florida state parks, WTP to control AIP, or how much demographics, knowledge and experience impact WTP.…”
Section: Discussionmentioning
confidence: 99%
“…Tate et al (2003) found that abundance of age-0 largemouth bass (Micropterus salmoides) increased with increasing coverage of aquatic vegetation in Florida lakes. Similar results have been reported across a variety of systems for a variety of fish species (e.g., Durocher et al 1984, Colle et al 1987, Killgore et ai. 1989.…”
Section: Introductionsupporting
confidence: 87%
“…1989. Although macrophytes provide a number of benefits, extremely high densities or extensive surface coverage of vegetation may have negative effects, including reduced growth and survival of fishes (Crowder andCooper 1982, Bettoli et al 1992), and may be a hindrance to recreational activities (e.g., swimming, boating; Colle et al 1987, Henderson 1996.…”
Section: Introductionmentioning
confidence: 99%
“…This example of an altered aquatic ecosystem caused by an invasive aquatic weed also negatively affects recreation and businesses that depend upon that human activity (Colle et al 1987). …”
Section: Altered Ecosystems and Recreational Opportunitiesmentioning
confidence: 99%